“Gunshot injury to the pelvis”. The bullet voided through the urethra - A Etabbal; A EL Shaikhy (Libyan International Medical University Journal)
Gunshot injuries (GSIs) are considered an emergency as life threatening. The gunshots injuries in the urinary tract are uncommon. The high-velocity of bullet can cause both a penetrating injury to the target organs as well as a blast injury to nearby structures, in addition to thermal injuries. In most cases, laparotomy is required to remove the bullet and to repair the injuries. The phenomenon of spontaneous migration of retained bullet to different parts of the body has been described in medical literature. Here, we present a patient who sustained penetrating GSI to the pelvis, without organ injuries, including the bladder. The bullet initially was retained within peri-vesical fat and the bladder wall while the mucosa remained intact, then it migrated into the bladder and came out through the urethra during voiding on the sixth day of the injury.